Shear strength of soft clay reinforced with polyethylene terephthalate (pet) column - Ng, Jun Shen (2024)
The unregulated usage of natural resources from years to years with the generation of waste has broughtsignificant adverse effects on the Earth. One of the recycling materials, Polyethylene Terephthalate (PET) plastic which can lead to environmental pollution has been seen increasing due to the large consumption of this material by humans. One of the sustainable methods to overcome the problem is to utilize the PET plastic in the geo technical property enhancement of kaolin clay S300, where this soil is weak in terms of its engineering characteristic. For this research, the aim was to investigate the use of PET plastic as granular columns beneath the soft kaolin clay acting as a reinforcement for the improvement of soil settlement, acceleration of pore water dissipation and increase of soil bearing capacity. The granular column construction was separated into two groups, which were single and group PET columns (consist of 3 columns). The specimens were tested in a small-scale laboratory model. Specifically, each group of PET column consists of two proposed diameters which are 10 mm and 16 mm. Before conducting the Unconfined Compression Test (UCT) and Unconsolidated Undrained (UU), the column parameters included the Area Replacement Ratio (Ac/As), Column Penetrating Ratio (Hc/Hs), Column Height to Column Diameter Ratio (Hc/Dc) and Volume Replacement Ratio (Vc/Vs) were first identified. From the total of 52 kaolin clay PET-reinforced specimens, each of the specimens had 50 mm diameter and 100 mm height with different PET column design while the unreinforced specimen was treated as a control sample. From the UCT results, the single PET column, the column with 16 mmdiameter and 1.0 Hc/Hs or 10.24 Ac/As showed the largest shear strength improvement, which recorded 56.53%. For group PET columns, the largest shear strength improvement recorded was 48.42% which had 12.00 Ac/As and 1.0 Hc/Hs. The UU test results which obtained from different confining pressures with 100kPa, 200kPa and 400kPa had shown that the 200kPa recorded the maximum deviator stress improvement for single and group category, recorded 94.48% and 86.21% respectively and these specimens were all had 0.8 Hc/Hs. For cohesion improvement, the trend was the same to previous shear strength parameters, 0.8 Hc/Hs for both single and group category showed the largest improvement,recorded 21.80% and 35.78% respectively while for friction angle improvement, the range was within 3.33 – 13.33% for single PET column and 4 – 10.67% for group PET columns. Coherent to that, the use of PET material had successfully proven this recycling material was a potential material for the substitution of non-renewable soil. The installation of single and group PET columns rectified the engineering properties of the kaolin clay soil by improving the shear strength parameters which was recorded in its unconfined compression stress, cohesion and soil friction angle. In short, the strength improvement of the kaolin clay soil resulted for the capability in withstanding the larger applied loads.